Determination of the renal clearance of inulin in rats: Lowered values at low urine flow rates - Barber, H. E. (1971)
The renal clearance of inulin (ClIN) was measured in anaesthetized male rats using a continuous intravenous infusion method. ClIN was independent of urine flow rate provided this was greater than 0·03 ml/minute. At flow rates lower than this, CIIN was reduced and appeared to correlate with the rate of flow. In experiments where a constant kidney function is required. e.g., pharmacokinetic studies, it is advisable to maintain urine, flow rates in the rat above 0·03 ml/minute.